BURDEN OF FAMILY CAREGIVER IN CARING FOR STROKE PATIENTS: A MIXED METHOD RESEARCH - Siti Na'imah; Christantie Effendy; Supriyati Supriyati (Jurnal Keperawatan Respati Yogyakarta, 2023)
Background: Stroke is the fifth leading cause of death in the world, stroke does not only have a negative impact on patients but also has an impact on family caregivers. This study aims to describe the burden experienced by family caregivers in caring for stroke patients. Methods: This research uses a mixed method with sequential explanatory approach. The research was conducted from August to October 2019 involved 106 family caregivers using a purposive sampling technique. Burden experienced was measured with the Zarit Burden Interview (ZBI) questionnaire. Quantitative data analysis was performed by SPSS and qualitative data analysis with Opencode. Results: Burden experienced was at a mild level, there was a significant relationship to education variables (p = 0.007, r = -0.297), family relationships (p = 0.001, r = 0.001), number of caregivers (p = 0.001, r = 0.364), and the patient's duration of stroke (p = 0.006, r = -0.322). There are three themes in this study, that is difficulties in caring, motivation for caring and sources of support. Conclusion: Although quantitatively the family caregiver experiences a mild burden, qualitatively the family caregiver reports complaints in caring for almost all aspects, so treatment is needed to resolve this burden.